In Search of Lost Lines: “Time Capsule” and the Epistolary Genre in Paul Auster’s Report from the Interior - Sara WATSON (E-REA)
The appearance of a certain number of early letters sent to Lydia Davis in Report From The Interior can seem surprising in a text which exposes the discovery of the outside world from the perspective of an interior subjectivity, since the added textual layers can appear almost overwhelming. However, by using the epistolary genre, Paul Auster manages not only to make the subtle game between the reader and the different incarnations of himself even more playful, but also to use the background of the European novel of the late 18th and early 19th centuries. Thus, he is able to question not only his self or himself, but the notion of the genre in which he is emmeshed, going so far as to uncover the possibilities of the hybrid nature of an autobiographical text which introduces a correspondence between two different versions of the author.